Delaunay Graph Based Inverse Distance Weighting for Fast Dynamic Meshing (Communications in Computational Physics, 2018)
A novel mesh deformation technique is developed based on the Delaunaygraph mapping method and the inverse distance weighting (IDW) interpolation.The algorithm maintains the advantages of the efficiency of Delaunay graph mappingmesh deformation while it also possesses the ability of better controlling the near surfacemesh quality. The Delaunay graph is used to divide the mesh domain into anumber of sub-domains. On each sub-domain, the inverse distance weighting interpolationis applied, resulting in a similar efficiency as compared to the fast Delaunaygraph mapping method. The paper will show how the near-wall mesh quality is controlledand improved by the new method.